The Moor as a Muslim in William Shakespeare’s Othello - Ghanim, Fawziya Mousa (European Journal of Social Science Education and Research, 2020)
The portrait of Muslim and Islam had an effective impact on the Elizabethan stage. It was dramatized paradoxically at the stage. Mostly , Muslims (Turk, Moors, Arabs and Persian) were represented as outsiders, infidels, lustful, violent people and barbarian. At the same time, they were regarded as a great threat to Europe, particularly after the expanses of Ottoman empire. The alliance of Queen Elizabeth with the Ottoman Empire represented by its Sultan Murad 11 had opened a new era of communication, policies and cultural exchange. The Elizabethan playwrights ’ writings and imagination were influenced by the tales and stories that narrated about Muslims and their actions. The stories were narrated by captives, travelers politician and traders. In addition, the Elizabethan people kept the Medieval distorted image towards Muslims’ characterization . William Shakespeare(1564-1616) portrayed a controversial image of a Muslim who converted to Christianity in his famous play Othello. The study aims at analyzing the Moor’s character as a Muslim and his paradoxical action throughout William Shakespeare’s Othello. The paper is divided into three sections; the first one is a brief introduction. It is concentrated on the western perspective of Islam, Prophet Muhammad and the eastern people, the second section deals with the Muslim’s visage on Elizabethan stage, the third section discusses the contradicting and paradoxical Islam-Christian image of Othello. The Conclusion sums up to the findings of the paper. Keywords : the Moor, Muslims, William Shakespeare and Othello 1.1.